Analisis Pelayanan Online Administrasi Kependudukan di Desa Cipete Kecamatan Cilongok Kabupaten Banyumas - Annas, Junaidi; Sutikno, Chamid; Pribadi, Indah Ayu Permana; Amanda, Ariesta; Millata, Chanifia Izza (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
This research analyzes online population administration services in Cipete Village, Cilongok District, Banyumas Regency. The research method used is qualitative with descriptive analysis. Using primary and secondary data collected through observation, interviews and documentation. The service theory used is the Zeithaml, Berry, and Parasuraman model in Hardiyansyah's book with 5 aspects: Tangible, Reliability, Responsiveness, Assurance, Empathy. The research results show that the Cipete Village Government, in this case the Adminduk as the village Admin, in serving population administration has not been able to serve residents optimally. The indicators of service that are not yet optimal are found in the aspect of reliability and discipline of the village administration in serving the community with online services, but the village government tries to serve residents with the old method, namely offline services, which causes the implementation of online services to be low.